Peran Lembaga Amil Zakat Ulil Albab Dalam Pemberdayaan Peserta Penerima Beasiswa Bagi Kaum Duafa Di Kota Medan - uswah hasanah (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2019)
This study aims to determine the role of LAZ UA in the empowerment of scholarship recipients for the duafa in Medan. Qualitative descriptive research type. Place of Taqwa Mosque Jl. Mongonsidi Gg A Medan and office Jl. Brigjed Katamso No 11 Medan. Techniques of collecting interview data, observation and documentation. Data analysis: reduction, display, verification. LAZ UA allocates some of its funds for scholarships. The obstacles of donor commitments are jammed in the middle of the road, and from the participants are not committed to the rules. The result is independence, provision of life-skills and fundamental changes in participants' attitudes.Keywords: poverty, LAZ Ulil Albab, empowerment of scholarship participants.